Preliminary Phytochemical Appraisal of Selected Medicinal Plants - Mohan, E; Suriya, S; Shanmugam, S; Muthupandi, CP; Rajendran, K (Journal of Drug Delivery and Therapeutics, 2021)
Preliminary phytochemical tests played a significant role in finding and locating chemical constituents which are source of pharmacologically active principles. By consider the medicinal importance of tuber of Acorus calamus, flower of Senna alata and fruit of Solanum torvum, the present study was designed to screen the phytochemical constituents present in such plant parts preliminarily. The phytochemical analyses were conducted by employing standard methods to detect the presence/absence of alkaloids, carbohydrates, flavonoids, glycosides, phenols, phytosterols, proteins, saponins and tannins. The results of present study revealed that alkaloids were found to be present in all the three plants analyzed and all the three solvents extracted, whereas, glycosides and phenols were absent. The acetone extract of Acorus calamus and Solanum torvum showed the presence more number of phytochemicals (4 each) and petroleum ether extract of Senna alata and Solanum torvum revealed the presence of only one compound. The potential active principles of the detected compounds should be quantified and pharmacologically evaluated.Keywords: Preliminary phytochemical analyses, Acorus calamus tuber, Senna alata flower, Solanum torvum fruit.